Genipap (Genipa americana L.) juice intake biomarkers after medium-term consumption. (November 2020) - Dickson, Livia; Tenon, Mathieu; Svilar, Ljubica; Fança-Berthon, Pascale; Martin, Jean-Charles; Rogez, Hervé; Vaillant, Fabrice
Graphical abstract: Highlights: Iridoids are the main metabolites after genipap juice intake. High inter-personal variability of excretion of genipic acid and D-8H genipinic acid. Composite biomarker based on multiple metabolites was relevant to genipap intake. Composed biomarker can be used for interpreting epidemiological studies. Abstract: Genipap ( Genipa americana L.) is an exotic fruit largely consumed and well known, in Amazonian pharmacopeia, to treat anemia, measles and uterine cancer. It is also used as a diuretic, digestive, healing, laxative and antiseptic. The aim of this study was to apply an untargeted metabolomics strategy to determine biomarkers of food intake after short-term consumption of genipap juice. Sixteen healthy adult men were administered jenipap juice (250 mL) twice a day for three weeks. Before and after the three weeks of consumption. the subjects drank a control drink, and they consumed a standard diet. Urine was collected after 0–6 h, 6–12 h and 12–24 h. An ultrahigh-performance liquid chromatography-mass spectrometry (UHPLC-MS)-based metabolomics approach was applied to analyze the urine samples. Principal components analysis (PCA) and partial least squares discriminant analysis (PLS-DA) were performed to highlight experimental differences between groups. The value of the area under the curve (AUC) of the receiver operator characteristic (ROC) curve validated the identified biomarkers. Thirty-one statistically affected urinary metabolites were putatively identified and were mainly related to iridoids family, medium-chain fatty acids, and polyphenols. Also a group of urinary markers including dihydrocaffeic acid (DHCA), 1-(4-hydroxyphenyl)-1, 2-propanediol and 3-carboxy-4-methyl-5-propyl-2-furanpropionic acid were established as biomarkers of genipap consumption. Our findings have established a comprehensive panel of changes in the urinary metabolome and provided information to monitor endogenous alterations that are linked to genipap juice intake. These data should be used in further studies to understand the health implications of genipap juice consumption.